Dryout avoidance control for multi-evaporator vapor compression cycle cooling. (15th December 2015) - Pollock, Daniel T.; Yang, Zehao; Wen, John T.
Highlights: Critical heat flux (CHF)/dryout constrains direct evaporative cooling efficiency. Systematic approach for active CHF avoidance control using temperature feedback. Two-loop, decentralized PI control for a multi-evaporator vapor compression cycle. Experimental validation of CHF avoidance control. Abstract: Two-phase cooling systems (e.g., pump-loops, vapor compression cycles) present a promising approach to the cooling of modern high power electronic systems. Such systems can achieve high coefficient of heat transfer but may incur dangerously high temperature when the imposed heat flux exceeds the critical heat flux (CHF). This paper presents a new control strategy that provides robust CHF avoidance in two-phase cooling for multiple evaporators under dynamic heat loads. This approach operates near the CHF to allow reduced coolant flow rates and greater system efficiency compared with the typical, and more conservative, open-loop or worst-case control strategies. The control architecture consists of two loops: an outer loop to determine evaporator mass flow rate demand, and an inner loop to supply and distribute the coolant using system actuators. Each control loop is implemented with feedforward based on static models as well as proportional–integral (PI) feedback controllers, and the decentralized approach allows scalable control design without the need for high fidelity nonlinear dynamic models. Simulations and corresponding experimental controller validations were conducted using a three-evaporator vapor compression cycle (VCC) testbed with transient imposed heat flux. The full closed-loop system is shown to be able to operate near CHF while avoiding CHF under transient heat flux, demonstrating both efficiency and robustness.